Tourism development through landscape theming: Exploring Art Nouveau experiences in Brussels - Kaat De Ridder; Dominique Vanneste (Journal of Tourism, Heritage & Services Marketing, 2020)
Purpose: This study aims to present and explore the landscape approach as an innovative management model for heritage tourism, applied to the case of the Brussels Art Nouveau heritage. The main objective of this paper is to gain insight in discrepancies regarding visions on the tourism potential of the Brussels' Art Nouveau and the Art Nouveau patrimony's integration within a (themed) tourism landscape. Methods: The research used an appropriate methodological approach for each of the stakeholder groups. The survey among visitors (N=105) was organized in the heart of Brussels and analyzed with statistical techniques (cross tabling and associations). Interviews (5) were conducted with key informants (policymakers, heritage managers and the Brussels DMO), after which content analysis was applied to the transcripts. Results: The research resulted in an innovative perspective to increase common ground between a landscape centered perspective with a focus on heritage and a tourismscape centered approach. The research deduced several hidden mismatches in perception and appreciation of the Art Nouveau and showed that there are major information and promotion problems, fostered by politically influenced fragmentation and lack of collaboration. Implications: By gaining insight in the visitor experience of a tourism product's potential, valuable knowledge is created for DMO's. The implementation of a themed landscape approach has the dual potential to increase the consistency of the heritage while developing a higher level of tourist experience.
Keywords: L82; Z33; 330; Art Nouveau; Brussels; landscape; theming; heritage tourism; tourism destination